Epigallocatechin 3‐gallate attenuates arthritis by regulating Nrf2, HO‐1, and cytokine levels in an experimental arthritis model. (5th December 2019) - Karatas, Ahmet; Dagli, Adile Ferda; Orhan, Cemal; Gencoglu, Hasan; Ozgen, Metin; Sahin, Nurhan; Sahin, Kazim; Koca, Suleyman Serdar
Abstract: Epigallocatechin 3‐gallate (EGCG) is a polyphenol that has been shown to have antioxidant and anti‐inflammatory effects. In this study, collagen‐induced arthritis (CIA) model, in Wistar albino rats, was used to elucidate the effect of EGCG on pathogenetic pathways in inflammatory arthritis. The levels of serum TNF‐α, IL‐17, malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx); the expression levels of tissue heme oxygenase‐1 (HO‐1) and nuclear factor erythroid 2‐related factor 2 (Nrf2); histopathologically, perisynovial inflammation and cartilage‐bone destruction were examined. In the sham group, serum TNF‐α, IL‐17, and MDA levels increased, while SOD, CAT, GPx levels, and the expressions of Nrf2 and HO‐1 decreased. On the other hand, in the EGCG administered groups, serum TNF‐α, IL‐17, and MDA levels improved, while SOD, CAT, GPx levels and the expressions of Nrf2 and HO‐1 increased. Moreover, histopathological analysis has shown that perisynovial inflammation and cartilage‐bone destruction decreased in the EGCG administered groups. These results suggest that EGCG has an antiarthritic effect by regulating the oxidative‐antioxidant balance and cytokine levels in the CIA model, which is a surrogate experimental model of rheumatoid arthritis. Abstract : EGCG applications, in experimental arthritis model, enhance the antioxidants enzyme levels and the expressions of Nrf‐2 and HO‐1. On the other hand, EGCG applications decrease the level of MDA, an oxidant, and the level of pro‐inflammatory cytokines. Moreover, EGCG ameliorates the clinical and histological findings of inflammatory arthritis.